The effectiveness of educational infographics on developing the skills of designing digital images for students of the Faculty of Education at Al-Aqsa University (Palestine Technical College Journal for Research and Studies, 2023)
This study aims at identifying The effectiveness of educational infographics on developing the skills of designing digital images for students of the Faculty of Education at Al-Aqsa University. The researcher prepared a cognitive test for instructional design, The study tool was an educational design cognitive test, and a note card to measure digital design skills for digital still images. It was applied to the study sample consisting of (45) students. They were selected intentionally and divided into two groups, one of them is control and the other is experimental. the results showed that there is a significant impact of using infographics techniques in developing designing skills of digital images in both cognitive and performance aspects, where the adjusted ratio of cognitive aspect reached 1.715 on Blake's scale which is higher than the ratio 1.2, on the other hand, the ratio of the performance aspect reached 1.651 on Blake's scale which is also higher than 1.2. This indicates that there is great effectiveness on using infographics techniques in developing designing skills of digital images for the students of faculty of education at Al Aqsa University.
Keywords: e-learning; infographic; digital design; digital images